The School milieu factors contributing to the second-language reading development of learners: Primary school teachers’ experiences in Botswana. school environment challenges for development of reading skills - Teane, Florah Moleko (Per linguam : a journal of language learning, 2024)
he study sheds light on the factors that contributes to the second language reading development of primary school learners. Concerns have been expressed regarding primary schools’ learners’ inability to read using second language. The situation is so intense that it impedes learners’ easy progression to higher levels because they have not acquired the communication and writing skills at lower classes. This paper outlines milieu enhanced factors that contributes to the dilemma. The study was qualitative in nature with a case of three primary schools used to investigate the phenomena. Purposeful sampling was used to sample 18 primary school teachers, six from each school. Face to face individual interviews were held with 10 teachers and two focus groups of nine participants each to source data. The findings revealed that school factors such as insufficient resources, teachers’ lack of expertise and preschool education contributed to low levels of reading development in children at lower primary schools. The study thus recommends the provision of resources in the form of reading material and teachers with expertise to enhance the teaching of second language reading skills. Sending children to preschools will be an added advantage. This study will be beneficial to teachers at primary schools, curriculum developers and the national policy makers.